Implementación de un sistema web para la gestión de ventas, con analítica de datos para la toma de decisiones en el almacén de ropa "NOVEDADES DOS HERMANOS" en el cantón La Maná. - Pallo Macias, Carla Noemi (2024)
The present research project was carried out with the purpose of solving the problems of the clothing warehouse "NOVEDADES DOS HERMANOS" which is located in La Maná Canton, Cotopaxi province since it does not have a computer system that automates the management of sales processes, inventories, products, customers, suppliers. So, the researchers proceeded to implement a web system for sales management applying data analytics focused on decision-making. For the development of the web system, the researchers based on the agile Scrum methodology, which allows them to work together with the warehouse needs. Consequently, this methodology shows flexibility because it permits to make modifications in the system when it is required, but always before the implementation. In the research, it was possible to determine the tools and programming languages that served for the development and system operation. So, it is vitally important to carry out an exhaustive analysis of the requirements in order to achieve the correct implementation of the web system. In this way, the following tools were used for the development: PHP, MySQL, Laravel and Microsoft Power Bi, these ones do not have cost. In addition, they adjust to the system requirements.